Mortalin deficiency suppresses fibrosis and induces apoptosis in keloid spheroids - Won Jai Lee (Nature Portfolio, 2017)
Abstract Mortalin (Mot) is a mitochondrial chaperone of the heat shock protein 70 family and it’s pro-proliferative and anti-apoptosis functions could be associated with keloid pathogenesis, and blocking of mortalin and its interaction with p53 might be a potential novel target for the treatment of keloid. Therefore, we generated mortalin-specific small hairpin (sh) RNAs (dE1-RGD/GFP/shMot) and introduced into keloid spheroids for examination of its apoptotic and anti-fibrotic effect. On keloid tissues, mortalin expression was higher than adjacent normal tissues and it’s protein expressions were activated keloid fibroblasts (KFs). After primary keloid spheroid were transduced with dE1-RGD/GFP/shMot for knockdown of mortalin, expression of type I, III collagen, fibronectin, and elastin was significantly reduced and transforming growth factor-β1, epidermal growth factor receptor (EGFR), Extracellular Signal-Regulated Kinases 1 and 2 (Erk 1/2), and Smad 2/3 complex protein expression were decreased. In addition, increased TUNEL activities and cytochrome C were observed. Further, for examine of mortalin and p53 interaction, we performed immunofluorescence analysis. Knockdown of mortalin relocated p53 to the cell nucleus in primary keloid spheroids by dE1-RGD/GFP/shMot transduction. These results support the utility of knockdown of mortalin to induce apoptosis and reduce ECMs expression in keloid spheroid, which may be highly beneficial in treating keloids.